Analisis Hukum Pidana Terhadap Praktik Grooming Anak di Media Sosial - Raden Suwito; Artukian Laila (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rise of social media has shifted the patterns of sexual crimes against children from physical spaces to the digital realm, notably through "child grooming"—a process where an adult perpetrator gradually establishes an emotional bond with a child for the purpose of sexual exploitation. This article analyzes the criminal legal framework regarding child grooming on social media in Indonesia, the forms of criminal liability for perpetrators, and the legal challenges in law enforcement and the formulation of ideal criminal policies. The study employs a normative juridical method, utilizing both statutory and conceptual approaches. The findings indicate that although Indonesia lacks a standalone offense for grooming, the constituent acts can be prosecuted cumulatively under the National Criminal Code, the Child Protection Law, the Law on Sexual Violence Crimes, and the Electronic Information and Transactions Law. The absence of a standardized definition for the grooming phase—specifically regarding stages prior to physical contact—makes the burden of proof reliant on judicial interpretation and hinders proactive law enforcement. Additional challenges arise from digital forensic evidentiary issues, stigma that discourages victim reporting, and a lack of inter-agency coordination. The article recommends establishing grooming as a distinct criminal offense modeled after the Lanzarote Convention, alongside strengthened procedural laws for electronic evidence and the implementation of "safety by design" requirements for digital platform providers.